2023
DOI: 10.1161/hypertensionaha.122.20602
|View full text |Cite
|
Sign up to set email alerts
|

Body Position and Orthostatic Hypotension in Hypertensive Adults: Results from the Syst-Eur Trial

Abstract: BACKGROUND: We recently demonstrated that more intensive blood pressure (BP) treatment lowered risk of orthostatic hypotension (OH) measured with a seated-to-standing protocol. However, seated-to-standing OH assessments are less sensitive than supine-to-standing and could miss clinically relevant OH. OBJECTIVES: Using data from the Syst-Eur trial (Systolic Hypertension in Europe), we examined the effect of hypertension treatment on incidence of OH based… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 32 publications
1
3
0
Order By: Relevance
“…Moreover, our findings are in line with the research of Grobman et al [20], Juraschek et al [21], and Earle et al [22], advocating for the application of orthostatic tests in diverse configurations to evaluate physical stress adaptation. This highlights the necessity of consistent evaluation of the autonomic nervous system in students, particularly under heightened stress scenarios like wartime conditions.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Moreover, our findings are in line with the research of Grobman et al [20], Juraschek et al [21], and Earle et al [22], advocating for the application of orthostatic tests in diverse configurations to evaluate physical stress adaptation. This highlights the necessity of consistent evaluation of the autonomic nervous system in students, particularly under heightened stress scenarios like wartime conditions.…”
Section: Discussionsupporting
confidence: 92%
“…In these circumstances, employing tests like 'supine to standing' and 'seated to standing' in different variations is advised. This method is recommended in several research papers [20,21,22], highlighting the need to evaluate the autonomic nervous system in college students, particularly under challenging conditions such as warfare, pandemics, and virtual education. This approach aids in comprehensively grasping and alleviating the effects of these situations on students' autonomic nervous health.…”
Section: Introductionmentioning
confidence: 99%
“…Excessive neurohormonal activation and sympathetic overactivity may be responsible for this observation 18 , 30 . Likewise, orthostatic hypotension, defined as a reduction in SBP of ≥ 20 or a reduction in DBP of ≥ 10 mmHg one minute after standing from a seated position, has also been shown to be associated with increased cardiovascular mortality 15 , 31 33 . Taken into context, our results highlight that by obtaining standing office BPs, a clinician can also utilize the advantage of increasing diagnostic accuracy for hypertension in addition to the important prognostic information provided.…”
Section: Discussionmentioning
confidence: 99%
“…77 Large hypertension treatment trials have used seatedto-standing rather than supine-to-standing BP protocols to detect OH. 19,20,63,78 Seated-to-standing protocols are included as an alternative method in many society guidelines, 16 and are more practical and easier to implement, particularly in ambulatory clinics and large clinical trials, but at the cost of decreased sensitivity 79 because OH is diagnosed more frequently from supine than from seated positions. 24,37,73,[80][81][82][83] Moreover, 1 study found that only supine-to-standing OH was associated with falls and orthostatic symptoms in adults ≥70 years of age (62% hypertensive).…”
Section: Diagnostic Protocols For Oh and Recommendations For Screeningmentioning
confidence: 99%